Customer trust, engagement, and swift guanxi on TikTok live streaming - Koeswanto, Matthew Malviano; Andajani, Erna; Rahayu, Siti (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2025)
With the rapid advancement of social media, there has been a significant transformation, particularly among customers who interact with certain brands, exemplified by the phenomenon of live-streaming on TikTok. The interactions within this medium reflect a dynamic relationship between broadcasters and customers, in which mutual trust is essential to sustaining customer engagement. The present research examines the influence of customer trust on customer engagement. Furthermore, it analyzes the role of swift guanxi in strengthening relationships among TikTok live-streaming users in Indonesia. A quantitative approach was used, with a population comprising TikTok users who had made purchases and interacted with other community members, and a sample of 205 respondents selected via purposive sampling. Respondent data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the measurement and structural relationships of the proposed model. The results showed that customer trust had a positive and significant effect on customer engagement, and swift guanxi also contributed to enhancing customer engagement. These findings indicate that interpersonal relationships between broadcasters and customers play an essential role in strengthening customer engagement on TikTok live streaming.